The Teacher's Attempt to Solve Imla’ Problems in Teaching the Arabic Language - Nikmatul Azizah; Kalis Rubeda, Syukril Agaba (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
The background of this study on the issue of Imla’ (dictitation) teaching in Arabic language teaching to seventh grade students is due to factors that influence dictation teaching. The purpose of this study is to identify the factors of dictation teaching and their solutions in Arabic language teaching at the Kediri State Islamic Secondary School. This research uses a qualitative research method. Data collection techniques include observation, interviews, documents, and descriptive analysis. The results of the study show that dictation in Arabic language teaching is carried out by writing new vocabulary on the blackboard, reading it, translating it, repeating it, and then assessing the dictation. The use of interactive activities, such as group discussions and peer feedback, can enrich the learning experience by encouraging collaboration and active engagement among students. Factors in dictation teaching include students' educational backgrounds, their lack of ability to understand dictation rules, their lack of understanding of the relationship between letters of the alphabet, the irregular distribution of letters, their lack of independence, and so on. Teachers' efforts to overcome spelling problems include: explaining spelling rules, providing motivation, training, memorising vocabulary, then writing and translating. Keywords: The teacher's attempt, Spelling problems, Teaching the Arabic language.